Moving together—benefits of a 12-week online dance training intervention on static and dynamic postural stability and gait speed in older women: an exploratory pre-post study - Hansen, Rasmus Kopp; Jochum, Elizabeth; Egholm, Ditte; Villumsen, Morten; Hirata, Rogerio Pessoto (Frontiers in Sports and Active Living, 2024)
Background Physical inactivity negatively affects gait performance and postural stability in older adults resulting in a higher risk of fall accidents. Previous research has shown that in-person dance training improves various aspects of balance and lower-extremity function, however, little is known about the potential benefits of dance training delivered online on variables used for fall risk stratification in older adults. We aimed to explore the benefits of a 12-week online dance training intervention on static and dynamic postural stability and gait speed in older women.Methods Forty-five older adults (44 women) were included in this exploratory pre-post study. The 12-week dance intervention consisted of two weekly 60-min classes in contemporary (improvisation) and salsa dance delivered online through Zoom video calls. Static and dynamic postural stability was assessed using the center of pressure (CoP) area and velocity (force platform), and the Mini Balance Evaluation Systems Test (Mini-BESTest), respectively. 10-m gait speed was measured using photo gates. Before and after comparisons were performed using paired sample ttests.Thirty-two older women completed the study. There were no significant changes for static postural stability assessed by CoP area or velocity (P ≥ 0.218, Cohen d ≤ 0.234). The Mini-BESTest total score was significantly improved at post-intervention (23.88 ± 3.01) compared to baseline (22.56 ± 1.41, P = 0.007, d = 0.52). 10-m gait speed was significantly faster at post-intervention (1.68 ± 0.25 m/s) compared to baseline (1.57 ± 0.22 m/s, P < 0.001, d = 0.737).Discussion Although some caution is needed due to the uncontrolled study design, the results indicate that online dance training has a small effect on static postural stability but may be beneficial for gait speed and in particular dynamic postural control among older women. While the absolute increase in gait speed suggests limited clinical relevance, the change in Mini-BESTest score may reflect a clinically meaningful enhancement of dynamic postural control.